A educação e o surgimento dos grupos escolares em Goiás: o caso grupo escolar Dr. Pedro Ludovico Teixeira (1934) e a educação formal em Goiandira - (:unkn) unknown (Universidade Federal de Goiás, 2018)
This study aims to understand how the implantation of the Dr. Ludovico Teixeira Group in 1934 was carried out in Goiandira, Goiás, in accordance with a school model that aimed at the process of nationalization and internalization of the country during the government of Getúlio Vargas. In Brazil, the political process in 1930 deposed Washington Luiz and brought Getúlio Vargas to power. From then on, the so-called Provisional Government (1930-1934) initiated the centralization of power and established a proposal for a reorganization of Brazilian politics, not representing a transformation in people's lives, but only an alternation of oligarchies in power. In education, this meant new educational policies and intervention using the discourse of education as a redeemer and solution to society. This reconstruction began by expanding the school into the interior. In Goiás, the creation of large-scale School Groups increased from 16 in 1929 to 38 in 1936. Thus, it is possible to verify that the installation of School group Pedro Ludovico in 1934 is part of a complex process of renovation in the education of the Government Vargas, with the purpose of direct intervention of the federal government in the process of nationalization of the country. Education has been a privileged locus for political actions of internalization. The School group now analyzed in the city of Goiandira represents a direct action of this interiorization project with strong nationalist content. The documentary corpus is formed by report, minutes, letters about the school groups and educational policies of the beginning of the Vargas Government, in addition to specifically, documents about the school group in Goiandira.
The education and the emergence of school groups in Goiás: the school group case Dr. Pedro Ludovico Teixeira (1934) and formal education in Goiandira
Keywords: Nacionalização; História da educação; República; Grupo escolar; Getúlio Vargas; CIENCIAS HUMANAS::HISTORIA